(untitled) (Contemporary Journal of Social Science Review, 2024)
Recent research in Positive Psychology has shown a significant link between Psychological Capital (PsyCap) and Mental Health (MH). However, the role of Perceived Social Support (PSS) in mediating this relationship, particularly within the context of higher education, has not been widely explored. This study aimed to investigate how PSS might mediate the influence of PsyCap on students’ mental health. Using a cross-sectional design, the research sampled 443 undergraduate and graduate students from the University of the Punjab, Lahore, Pakistan. The findings, analysed through Partial Least Squares Structural Equation Modeling (PLS-SEM), revealed that both PsyCap (β = 0.815, t = 31.074, p < 0.000) and PSS (β = 0.405, t = 28.051, p < 0.000) positively impacted students’ mental health. Additionally, PSS was identified as a meaningful mediator between PsyCap and mental health (b = 0.080, t = 2.319, p < 0.020). These results underline the importance of fostering both PsyCap and PSS in academic environments to improve student well- being. The findings provide valuable insights for university faculty, psychologists, and curriculum developers, stressing the need to integrate these elements into educational and support programs. By focusing on PsyCap and social support, higher education institutions can create environments that promote mental health and overall student success. This aligns well with growing concerns in academic settings about the mental well-being of students and offers a path forward for practical, evidence-based interventions. These results contribute to the understanding of how psychological and social factors intersect, presenting opportunities for further research and implementation in similar academic settings.